2003
DOI: 10.1029/2002jb001872
|View full text |Cite
|
Sign up to set email alerts
|

The strength and rheology of methane clathrate hydrate

Abstract: [1] Methane clathrate hydrate (structure I) is found to be very strong, based on laboratory triaxial deformation experiments we have carried out on samples of synthetic, high-purity, polycrystalline material. Samples were deformed in compressional creep tests (i.e., constant applied stress, s), at conditions of confining pressure P = 50 and 100 MPa, strain rate 4.5 Â 10 À8 _ e 4.3 Â 10 À4 s À1 , temperature 260 T 287 K, and internal methane pressure 10 P CH4 15 MPa. At steady state, typically reached in a few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
224
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(245 citation statements)
references
References 31 publications
9
224
1
1
Order By: Relevance
“…Working from a solid foundation of knowledge obtained from earlier studies (Sloan and Koh, 2008;Boswell, 2007), researchers gained a greater understanding of the complexity of hydrate accumulations through laboratory work (Waite et al, 2002;Durham et al, 2003;Winters et al, 2004;Gupta et al, 2006), numerical simulation analyses (Moridis and Reagan, 2007a,b;Moridis and Sloan, 2007), and national and international collaborative field experiments (Dallimore and Collett, 2005) (see discussion in following sections of this paper), and began the development of the precursors to tomorrow's hydrate exploration and evaluation technologies. By 2005, it was clear that, given certain reservoir conditions, production of methane from hydrate was technically feasible and potentially commercially viable through specially tailored application of existing technologies (Boswell, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working from a solid foundation of knowledge obtained from earlier studies (Sloan and Koh, 2008;Boswell, 2007), researchers gained a greater understanding of the complexity of hydrate accumulations through laboratory work (Waite et al, 2002;Durham et al, 2003;Winters et al, 2004;Gupta et al, 2006), numerical simulation analyses (Moridis and Reagan, 2007a,b;Moridis and Sloan, 2007), and national and international collaborative field experiments (Dallimore and Collett, 2005) (see discussion in following sections of this paper), and began the development of the precursors to tomorrow's hydrate exploration and evaluation technologies. By 2005, it was clear that, given certain reservoir conditions, production of methane from hydrate was technically feasible and potentially commercially viable through specially tailored application of existing technologies (Boswell, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…China has pursued gas hydrates R&D for more than a decade (Fan et al, 2005) and conducted its initial drilling and coring program in the South China Sea in early 2007. That expedition found saturations of gas hydrate up to 40% in undeformed, clay-dominated sediments at a number of sites .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers hypothesized that the bubble fabric forms when hydrate-coated gas bubbles collect during ascent through the sediment. Pure methane hydrate is much stronger than ice (Durham et al 2003); however, a bubble fabric likely has a very different geomechanical response. Although the presence of free gas has a solid foundation, the reason for it is still debatable.…”
Section: Hydrate Formed From High Gas Fluxmentioning
confidence: 99%
“…Gas hydrates are seen as future generation energy resource [2]. Keeping into this various studies have been reported gas hydrates as potential energy resource [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. According to USA department of energy, if only feeble amount of the methane stored in the hydrates can be obtained, it will be more than the current domestic supply of USA of natural gas [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that under the sea huge amount of methane of the order of trillion in the form of gas hydrate is present [1]. Hydrates are naturally occurring materials that are present on submarine continental margins and regions of Arctic permafrost [2][3][4]. Their presence is also supposed to be on large icy to medium-sized moons of the outer solar system [5,6] and also on the polar regions of Mars [7,8].…”
Section: Introductionmentioning
confidence: 99%